Lintas revolusi fisik tahun 1945-1949 daerah Kalimantan Selatan di hulu Sungai Selatan/Djarani E.M.,Burhanuddin Soebely ; editor Djarani E.M....[et al} - JARANI, E.M. (2001)
xvi, 300 hlm. ilus. 23 cm.